Influence analysis of elastic deformations of the track cable on efforts in the hauling rope of aerial ropeway - Raksha, S. V.; Goryachev, Yu. K.; Kuropyatnik, A. S. (Science and Transport Progress, 2013)
Purpose. To estimate influence of elastic deformations of the track cable arising at movement of cars, on effort in a hauling rope of the aerial ropeway. Methodology. The method of consecutive approaches was used for research influence of elastic deformations of a track cable on effort in a hauling rope. Thus, definition of a tension of a track cable was carried out with use of the technique based on principles of modular configuration, the essence of which consists in formation of mathematical model by a combination of blocks of the formulas describing balance of the track cable on supports. Findings. The research has shown that influence of elastic deformations of a track cable on effort in a hauling rope was insignificant (less than 1 %). That points to possibility not to consider change of the track cable length, caused by its elastic properties, when modeling loading of elements of system «drive – traction rope – tension device». Also it has been found that use of the tension device of a track cable increased influence of its elastic properties on loading of rope system elements. At the same time the elastic component of the track cable tension in the test flight does not depend on a car position in the adjacent span, but only determines by the parameters of the rope system. Originality. The possibility of excluding the changes of track cable length caused by its elastic properties, when modeling loading of elements of system «drive – traction rope – tension device» was proved. Practical value. The use of these techniques and the results will simplify the mathematical model of loading of elements of the cable system and the system «drive – traction rope – tension device» as a whole.